Analisis Proksimat dan Serat Kasar Sereal Instan Beras Hitam, Tempe, dan Brokoli bagi Penderita Diabetes Melitus Tipe 2 - Arindra Nirbaya; Yosfi Rahmi; Titis Sari Kusuma (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2026)
Type 2 diabetes mellitus (T2DM) is a metabolic disorder characterized by insulin dysfunction. Dietary support is essential to control blood glucose levels, prevent malnutrition, and reduce complications. Black rice is rich in dietary fiber and antioxidants that help regulate blood glucose and reduce oxidative stress. Tempeh, a fermented soybean product, contains essential and bioactive amino acids that contribute to glycemic stability. Broccoli provides chromium, which improves insulin sensitivity. This study aimed to analyze the nutritional quality and crude fiber content of BTB instant cereal (black rice, tempeh, and broccoli) for patients with T2DM. The research employed a quantitative laboratory experimental approach using a completely randomized design (CRD) with three treatment levels (P1, P2, and P3) based on different proportions of black rice, tempeh, and skim milk. All formulations were evaluated for organoleptic properties, proximate composition, and crude fiber content. The results showed that variation in ingredient proportion significantly affected protein (α = 0.003) and carbohydrate (α = 0.015), while there were no significant differences in fat (α = 0.148), water (α = 0.153), ash (α = 0.202), energy (α = 0.274), and crude fiber (α = 0.271). Based on the dietary standards of the Indonesian Endocrinology Association (PERKENI), the P2 formulation demonstrated the most optimal nutritional profile, with protein of 10.48 ± 0.67%, fat of 24.64 ± 1.98%, carbohydrate of 58.31 ± 0.93%, energy of 489.68 ± 9.59 kcal, and crude fiber of 2.52 ± 0.29 g. Therefore, it was concluded that BTB instant cereal has potential as an alternative breakfast option for individuals with T2DM.